Ocena polisemii terminologicznej w świetle rozwoju nauk = Assessment of terminological polysemy in the light of the science development - Jankowiak, Lucyna Agnieszka (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article draws attention to the unreliability of the distance of sciences criterion in assessing terminological polysemy in light of the science development. In the view of H. Jadacka (three degrees of ambiguity) and E. Grodzinski (good and bad polysemy), this criterion determines the distinction of acceptable terminological polysemy. However, it turns out to be misleading, as the article proves with the example of terms from medicine and veterinary medicine. That is, disciplines that developed as a single science until the end of the 18th century but today constitute separate disciplines and belong to two different sets of sciences. The application of the criterion of the distance of sciences when characterising (diachronic and synchronic) terminology may cause the polysemy of the same term (e.g. endosperm) to be assessed differently at different stages of the development of a given science (here: medicine and veterinary medicine).
Keywords: historia nauk; historia terminologii; polisemia terminologiczna; history of sciences; history of terminology; terminological polysemy